2019
DOI: 10.1016/j.jpsychires.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Does the frequency of administration of long acting injectable antipsychotics impact psychiatric outcomes and adverse effects: A systematic review and meta-analysis

Abstract: words)Dosing regimens for depot antipsychotics range from two-to twelve-weekly administration.There are limited meta-analytic data regarding the effect of different injection frequencies of the same depot antipsychotic at the equivalent dose on psychiatric outcomes and adverse effects. This study investigated differences in psychiatric outcomes and adverse effects between different frequencies of depot antipsychotics through a systematic review and metaanalysis. We performed a systematic search of MEDLINE, EMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“… Investigator-rated injection site reactions for PP3M vs PP1M: Induration (12% vs 10%), redness (10% vs 9%), swelling (7% vs 9%). 12 Ting et al (2019) 27 Olanzapine q2w or q1M Paliperidone q1M or q3M Fluphenazine Aripiprazole q1M Risperidone q2w Q2w injections were less likely to cause injection site pain than q1M injections (finding from sensitivity analysis). Abbreviations: q1M, once-monthly; q3M, every 3-months; q2w, every 2 weeks; FGAPs, first generation antipsychotics.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Investigator-rated injection site reactions for PP3M vs PP1M: Induration (12% vs 10%), redness (10% vs 9%), swelling (7% vs 9%). 12 Ting et al (2019) 27 Olanzapine q2w or q1M Paliperidone q1M or q3M Fluphenazine Aripiprazole q1M Risperidone q2w Q2w injections were less likely to cause injection site pain than q1M injections (finding from sensitivity analysis). Abbreviations: q1M, once-monthly; q3M, every 3-months; q2w, every 2 weeks; FGAPs, first generation antipsychotics.…”
Section: Resultsmentioning
confidence: 99%
“…Injection site reactions and pain were infrequent, low and mild, and were similar between the PP1M and the PP3M, regardless of the dose and of the volumen or location of the injection. The systematic reviews and meta-analyses conducted by Kisely et al 24 and Ting et al 27 comparing several types of LAI antipsychotics, reported that 2 weekly administration was less likely to lead to injection site pain than 4 weekly administration. The studies by Hay 17 and Jones et al 18 both reported clinically significant reactions such as pain, bleeding, nodules, thickening, hematoma and indurations primarily associated with the administration of haloperidol decanoate, although these were not significantly different from those reported with other depot antipsychotics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations